Pengembangan Media Pembelajaran Kotak Pintar Dengan Multimedia Pada Materi Perkalian dan Pembagian di Kelas III Sekolah Dasar - Resti Laila Hasanah; Melva Zainil; Alwen Bentri; Salmaini Syofyan (Universitas Negeri Padang, 2025)
This study was motivated by the limited use of concrete media integrated with technology in mathematics learning for third-grade elementary students, indicating the need for innovative learning media. The research aimed to develop a multimedia-based “smart box” learning media that is valid, practical, and effective for teaching multiplication and division in the Merdeka Curriculum. The study used a Research and Development approach with the ADDIE model, involving the stages of analysis, design, development, implementation, and evaluation. The subjects were third-grade students from SDN 40 Korong Gadang, SDN 42 Korong Gadang, and SDN 22 Ulak Karang Utara. Data were collected through expert validation sheets, practicality questionnaires, and pretest–posttest assessments. The results showed that the developed media was categorized as valid based on evaluations from material experts (92.9%), media experts (80%), and language experts (95%). Practicality tests indicated that the media was very practical according to teachers (97.5%) and students (91.85%). The effectiveness of the media was shown by an increase in the average learning outcomes from 70 in the pretest to 94.57 in the posttest with an N-Gain score of 0.8 (high category). These findings indicate that the multimedia-based smart box learning media is valid, practical, and effective in supporting interactive mathematics learning for third-grade elementary students.